Validación del efecto de la concentración de óxido de cobre (x) en mezcla con dióxido de titanio (tio2)(1-x) (cuo)(x) para la inactivación fotocatalítica de e. coli en presencia de luz visible (2018)
In this project it was validated that titanium dioxide films in a mixture with copper oxide inactivated 99.99% of E. coli bacteria continuing the same methodology of the project "Evaluation of the effect of copper oxide concentration (x) in mixtures with titanium dioxide (TiO2)(1-x) (CuO)(x) on the microbicidal activity in presence of visible light ". The samples were 0.62%, 1.56% and 2.49% separately, were 0.62%, 1.56% and 2.49%. A preliminary test is carried out to prove its functionality, methylene blue is degraded. It is obtained that the mixture with 0.62% of precursor is the one that best degrades methylene blue. Inactivation of E. coli was performed with the 2.49% film on two culture media (nutritive agar, trypticase soy agar), obtaining percentages of inactivation from 32.5% to 38%. The method followed is not repeatable or reproducible, the results were compared with those obtained by Miguel Chávez and Gabriel Vivas using the same Methodology do not agree. However, the use of different culture media does not alter the result.